Analisis Bahaya Zina dalam Kitab Mahfudzot Fadhoilul Iman : Perspektif Moral dan Spiritualitas serta Strategi Pencegahannya dalam Kehidupan Sehari-hari - Hanifa Nur Laili; Ainur Rofiq Sofa (Tabsyir: Jurnal Dakwah dan Sosial Humaniora, 2025)
This study examines the dangers of zina (adultery) in the Kitab Mahfudzot Fadhoilul Iman with a focus on the moral and spiritual perspectives contained within it, as well as identifying strategies for preventing zina in daily life. The Kitab Mahfudzot Fadhoilul Iman depicts zina as a major sin that not only damages personal integrity but also disrupts social harmony and moral order within society. From a moral perspective, zina is viewed as a violation of purity, honor, and decorum in Islam, which can destroy relationships between individuals and degrade the quality of social life. Spiritually, zina is considered an act that blocks one from God's mercy, hardens the heart, and distances the individual from worldly and spiritual happiness. This research also identifies several prevention strategies based on the teachings in Kitab Mahfudzot Fadhoilul Iman, including strong religious education from an early age, maintaining proper interactions and modesty between men and women, strengthening worship and prayers as protection from temptations, and encouraging lawful marriage as a solution to safeguard purity. The findings emphasize the importance of applying the moral and spiritual values found in Islamic teachings to prevent the dangers of zina and maintain personal purity in daily life, which can contribute to the creation of a healthier and more harmonious society.